Construction and characterization of avian papillomavirus L1 virus-like particles - Abdul Latif, Nur 'Atikah (2021)
Papillomaviruses (PVs) are a large group of pathogens that foster the proliferations of cells into urogenital or skin tumours in a wide spectrum of vertebrate species. Host-switching and broad host range were becoming more common in PVs than expected. Information on avian papillomavirus (AvPV) especially on their molecular and structure are still lacking due to insufficient study on the papillomavirus viral infection and detection among avian species compared to human papillomaviruses (HPV). This study focuses on molecular analysis of the L1 gene which is the most conserved region in the viral genome of AvPV. Potential discovery of novel papillomavirus in avian species will enable development of a specific model research that can be referred to as a probe to screen for papillomavirus infection in avian as well as expanding the current papillomavirus taxonomy or genome databank. In addition, little is known about its protein ability in self-assembling into capsid protein as observed in L1 protein of HPV. The main objective of this study is to assess the self-assembling properties of recombinant avian papillomavirus L1 capsid protein in the E. coli expression system. Fresh faecal samples and cloacal swabs from Rockhopper penguins (Eudyptes chrysocome) that showed papillomatosis symptoms were sampled. Then, the DNA was isolated and sent for sequencing. The sequencing result was then analysed by multiple sequence alignment (MSA). The L1 sequence of the Rockhopper penguin Eudyptes chrysocome papillomavirus (EcPV) was then submitted to GenBank with accession number MW715602. In this study, the phylogenetic analysis will provide more understanding of the evolutionary pattern of the L1 gene from Rockhopper penguin (Eudyptes chrysocome)’s papillomavirus. The L1 gene was further chemically synthesized as the template of interest. The synthesized gene then was amplified by polymerase chain reaction (PCR) before being cloned into pTrcHis2-TOPO expression vector. The recombinant plasmid was then transformed into E. coli TOP10 competent cells. Positive transformants were verified by colony PCR, restriction endonuclease digestion using NcoI enzyme and sequencing. Expression of the L1 capsid proteins was induced by isopropyl β-d-1thiogalactopyranoside (IPTG) and analysed by sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting using mouse monoclonal antibodies targeting the His-tag. The proteins have been purified using sucrose density ultracentrifugation, immobilized metal affinity chromatography (IMAC) and size-exclusion chromatography by fast protein liquid chromatography (SEC-FPLC) before evaluating the assembling ability of the recombinant capsid proteins into virus-like particles (VLPs) by transmission electron microscopy (TEM). The L1 conserved region within another AvPV sequence has been validated by multiple sequence alignment (MSA). Results also showed that the amplified L1 EcPV capsid gene with the size of 1578 bp was successfully cloned and transformed. The L1 protein was expressed in the E. coli expression system producing approximately 37 kDa products. The purified recombinant L1 EcPV proteins were able to self-assemble into VLPs with size ranging from 30 – 50 nm. Different purification techniques gave different yields, whereby IMAC purification showed the most distinct self-assembled particles under TEM. Analysis and characterization of this L1 capsid protein is crucial for possible development of virus-like particle-based vaccines and immunological studies for AvPV.